False-positive Aspergillus galactomannan and its kinetics in allogeneic hematopoietic stem cell transplantation. Issue 5 (May 2015) - Kimura, Shun-ichi; Akahoshi, Yu; Nakano, Hirofumi; Harada, Naonori; Kameda, Kazuaki; Ugai, Tomotaka; Wada, Hidenori; Yamasaki, Ryoko; Ishihara, Yuko; Kawamura, Koji; Sakamoto, Kana; Ashizawa, Masahiro; et al.
Summary: Objectives: We evaluated the incidence of and risk factors for false-positive Aspergillus galactomannan (GM) antigenemia in allogeneic hematopoietic stem cell transplantation (HSCT). We also focused on the GM index value and its kinetics. Methods: Patients who underwent their first allogeneic HSCT at our center between June 2007 and December 2012 were included (n = 172). Episodes of positive GM tests were classified as either "true-positive", which fulfilled the EORTC criteria for proven or probable invasive aspergillosis (IA), or "false-positive", which was not accompanied by clinical findings. The remaining cases were regarded as "inconclusive". Results: The one-year cumulative incidences of IA and positive GM tests were 10.1% and 48.1%, respectively. Among 148 episodes of positive GM tests, 97(65.5%), 23(15.5%), and 28(19.0%) were classified as false-positive, true-positive and inconclusive, respectively. In the first episodes of positive GM tests in each patient (false-positive = 67, others = 30), an increase in the GM value in the first two measurements, neutropenia, and use of anti-mold agents at positive GM episode were associated with a significantly lower possibility of false-positive results according to a multivariate analysis. Conclusions: A false-positive GM test was frequently seen after allogeneic HSCT. An increase in the GM value may increase its positive predictive value. Highlights: We studied false-positive Aspergillus galactomannan in allogeneic HSCT recipients. We focused on galactomannan index value and its kinetics. A false-positive galactomannan test was frequently seen after allogeneic HSCT. Increase in galactomannan was associated with reduced false-positive results.